EFFECTIVE USE OF EDUCATIONAL METHODS IN STUDENT UPBRINGING - Masuma Zakirova Qahramon qizi (Web of Journals Publishing, 2024)
This article discusses the importance and effective use of educational methods in the upbringing of students.
Keywords: upbringing, method, student, methods of upbringing, educational process, educator, interactive.